Association of Intestinal Parasite Infection and Environmental Sanitation - Marusaha Selamet Wijaya; Lambok Siahaan; Inke Nadia (Buletin Farmatera, 2023)
Abstract: Intestinal parasitic infection is a problem that is still widely encountered in health-related communities with a fairly high morbidity rate of 411 per 1,000 population in Indonesia and 12.5% in the city of Medan. The cause is due to protozoan infection and to helminthiasis. Transmission of parasitic infections has risk factors that greatly influence, namely personal hygiene, residence, access to health education, family education, shoe wearing habits, hand washing practices, toilet availability, availability of clean water and defecation practices. This study was conducted to determine the relationship between intestinal parasitic infections and environmental sanitation at Helvetia Health Center, Labuan Health Center, Martubung Health Center. Analytical conservation (Chi-Square) with cross-sectional design. At least 100 people met the inclusion criteria. Data from surveys are results obtained over time from survey respondents' responses and information from survey participants' stool samples examined under a microscope using lugol and diethyl ether. From a total of 100 samples, it was found that 8 (8%) people suffered from intestinal parasitic infections with Trichuris trichiura 1 (1%), Hookworm 3 (3%), and Blastocystis 4  (4%). There were 100 (100%) samples that had good sanitation. No significant association was found between intestinal parasitic infection and environmental sanitation in the study sample (p = 0.08). There is no relationship between intestinal parasitic infections and environmental sanitation.